Análise do torque e da força axial, em diferentes condições de corte durante o rosqueamento de dois ferros fundidos cinzentos (CrCuSn e CrCuSnMo) e um ferro fundido vermicular da classe 350 - Pereira, Igor Cézar (2010)
The tapping operation is a complex cutting process when compared to other conventional processes like drilling, milling and turning. Furthermore, there are few publications about the effect of cutting conditions for this operation. For that reason, one of the objectives of this work is to gather information and knowledge about the phenomenon involved in the tapping operation. The workpiece materials used in this work are also the result of recent development of the manufacturing industry and are applied mainly in the production of heads for engine motors. The main objective of this work is to compare the torque and axial force when machining three different materials, two alloyed gray cast iron (CrCuSn and CrCuSnMo) and one compacted graphite iron. It was used high speed cutting tools with three straight flutes (ISO M6x1) TiAlN coated. It was investigated the effect of cutting speed, form of application and the type of the cutting fluid. The results show the decrease of torque and increase of axial force with cutting speed. The CrCuSn alloyed gray cast iron was the most difficult to cut material, concerning torque, when no cutting fluid is applied. It was also investigated in this work the effect of axial feed rate, concentricity error of tap and hole, tap geometry, type of coating and machined length on torque and axial force.